Relationship Of Nutritional Status Of Pregnant Women With Stunting Events In The Working Area Of Maja Pesawaran District - Eka Ana Marlian; Astriana Astriana; Vida Wira Utami (ANJANI Journal (Medical Science & Healthcare Studies), 2022)
Latar Belakang: Kependekan yang terjadi dalam periode kritis: seribu hari pertama sejak dalam kandungan sampai usia 2 tahun, bila tidak ditanggulangi akan berdampak permanen atau tidak dapat dikoreksi. Data stunting Kabupaten Pesawaran di tahun 2018 sebesar 35.28%, penyebab stunting salah satunya adalah gizi saat ibu hamil adapun tujuan dalam penelitian ini yaitu diketahui hubungan Status gizi ibu saat Hamil dengan kejadian Stunting di Wilayah Kerja Puskesmas Maja Kabupaten Pesawaran tahun 2020. Metode: Jenis penelitian analitik kuantitatif dengan pendekatan Cross Sectional, subjek dalam penelitian ini adalah seluruh balita usia 6-23 bulan. berjumlah 319 anak dan sampel 124 balita, tekhnik sampling proportional sampling. Obyek dalam penelitian adalah kejadian stunting dan status gizi ibu saat hamil. Penelitian telah dilaksanakan bulan Agustus di Wilayah Kerja Puskesmas Maja Kabupaten Pesawaran tahun 2020. pengumulan data dengan lembar ceklist. analisis data secara univariat dan bivariat (chi square). Hasil peneltian: diketahui sebanyak 21 (16,9%) responden balita stunting dan tidak stunting sebanyak 103 (83,1%) responden balita stunting, diketahui sebanyak 33 (26,6%) status gizi saat ibu hamil tidak normal dimana LiLA dengan ukuran ≤23,5 cm dan sebanyak 91 (73,4%) balita dengan status gizi ibu saat hamil normal dimana LiLa dengan ukuran 23,5 cm.Kesimpulan terdapat hubungan status gizi ibu saat hamil dengan kejadian stunting pada anak usia 12 - 59 bulan di Wilayah Kerja Puskesmas Maja Kabupaten Pesawaran tahun 2020. (P-Value 0,000 : OR 23,109)Saran Peningkatan peran program desa seperti Dasa Wisma keluarga dalam pencegahan stunting dengan pemberian makanan bagi keluarga tidak mampu yang ada di kelompok ABSTRACTIntroduce: Shortness that occurs in the critical period: the first thousand days from conception until the age of 2 years, if not addressed, will have permanent or irreversible impacts. The stunting data of Pesawaran District in 2018 was 35.28%, one of the causes of stunting was nutrition during pregnant women, as for the purpose of this study, namely to know the relationship between maternal nutritional status during pregnancy and the incidence of stunting in the Work Area of Maja Health Center, Pesawaran Regency in 2020.Methode: This type of quantitative analytic research with a cross sectional approach, the subjects in this study were all toddlers aged 6-23 months. totaled 319 children and a sample of 124 toddlers, sampling technique proportional sampling. The object of this research is the incidence of stunting and nutritional status of mothers during pregnancy. The research was conducted in August in the Work Area of the Puskesmas Maja, Pesawaran Regency, in 2020. data collection using a checklist sheet. data analysis by univariate and bivariate (chi square)The results: of the study showed that as many as 21 (16.9%) respondents were stunting and non-stunting as many as 103 (83.1%) respondents under five with stunting, it was known that 33 (26.6%) nutritional status when pregnant women were not normal where LiLA with size ≤ 23.5 cm and as many as 91 (73.4%) children under five with normal maternal nutritional status while LiLa was 23.5 cm in size.Conclusion there is a relationship between the nutritional status of mothers during pregnancy and the incidence of stunting in children aged 12 - 59 months in the Work Area of the Maja Puskesmas, Pesawaran District, 2020. (P-Value 0,000: OR 23,109) Suggestion Increasing the role of village programs such as Dasa Wisma family in preventing stunting by giving food for poor families in the group